Beyond traditional consumer research - current adoption and next steps for neuromarketing - Puprediwar, Pratik B.; Tapas, Poornima (Zielona Góra: Faculty of Economics and Management Press)
Purpose. Neuroscience used for conducting market research is called Neuromarketing. Though the effectiveness of Neuromarketing over traditional research has been proven, its adoption is very limited. The automotive sector is one of the biggest industries worldwide and due to lack of detailed research on the adoption of Neuromarketing in the Automotive space, authors have tried to bridge this gap. They have identified the current adoption of Neuromarketing and have suggested solutions to overcome barriers.
Keywords: Neuromarketing; Automotive; Adoption; Consumer neuroscience